Pulmonary Function and Serum Carboxymethyl-Lysine Level Evaluation in Acromegaly Patients - YAVUZ, DİLEK; KARAKURT, SAİT (TURKIYE KLINIKLERI, 2021)
Objective: We aimed to evaluate the pulmonary function tests (PFTs) and serum carboxymethyl-lysine (CML) level and their association with the disease activity in patients with acromegaly. Material and Methods: This cross-sectional study included 65 acromegalic patients (F/M:28/37) and 52 controls ( F/M:23/29). PFTs such as spirometry and diffusing capacity of the lungs for carbon monoxide (DLCO) were performed to determine the lungs' ability to exchange gases. Serum CML levels were measured with the enzyme-linked immunosorbent assay. Basal and nadir growth hormone (GH), hemoglobin A1c (HbA1c), and insulin-like growth factor-1 (IGF-1) were also assessed. Results: Serum CML levels were significantly higher in acromegalic patients (208.1 +/- 80 ng/mL) than in controls (174.2 +/- 11 ng/mL), (p=0.02). The evaluated PFTs were expressed as predicted values [forced expiratory volume in the 1st second % (p=0.01), forced vital capacity % (p=0.007), functional residual capacity % (p=0.03), residual volume % (p=0.03), vital capacity % (p=0.007), total lung capacity % (p=0.01), and DLCO% (p=0.02)) that were found to be elevated in acromegalic patients than in controls. CML levels positively correlated with HbA1c (r=0.53, p=0.02) but did not con-elate with basal GH levels (r=0.35, p=0.06). GH and IGF-1 levels positively correlated with lung volume in acromegalic patients. Conclusion: Serum CML levels increased in acromegaly patients but had no association with the PFTs results. Increased lung volume was the most prominent lung function alteration in acromegalic patients; relevantly, we found elevated GH and IGF-1 levels to be associated with the increased lung volumes. Future studies need to evaluate the association between the advanced glycation end-products and complications of acromegaly.
Keywords: Acromegaly; pulmonary function tests; growth hormone; insulin-like growth factor-1; carboxymethyl-lysine; GROWTH-HORMONE